Reversible Data Hiding using RIT, AES and UES Frame Work - Bansal, Akanksha; Ramiya, Manoj; Tiwari, Nirupma (International Journal of Computer Sciences and Engineering, 2025)
Image Steganography is an emerging field in computer science. There is a need of secured data transmission system to protect the data and maintain the privacy. This work is based on multilevel security method. The reversible data hiding has been implemented using a robust method. The secret image is encrypted using Reversible Image transformation, followed by AES (Advanced Encryption Standard) algorithm and finally the UES( Unified Encryption and Scrambling) is applied for data embedding into the carrier image. The secret key is also added to the encrypted image and it further makes the frame work more robust. The frame work is simulated using MATLAB and the statistical results like PSNR, MSQE and SSIM confirm the proposition